Enhanced bone regeneration using sodium alginate and polyvinyl alcohol incorporating TiO2 nanoparticles composite film for orthopedic application - Guoying Zhang; Xunkai Hou; Zhen Geng; Mahani Yusoff; Nur Adibah Roslan; Mohd Hasmizam Razali (Results in Chemistry)
Bone tissue regeneration remains a significant challenge in orthopedic medicine due to the limited osteogenic and antimicrobial properties of conventional biomaterials. This study presents an innovative approach to prepare nanocomposite film involving sodium alginate (SA) and polyvinyl alcohol (PVA) blend polymers reinforced with titanium dioxide nanoparticles (TiO2NPs) at varying concentrations (0 wt%, 1 wt%, 5 wt%, 10 wt, and 15 wt%) using solvent casting method. Among these, the PVA + SA@10 wt%TiO2NPs nanocomposite film exhibited exceptional bioactivity and antibacterial properties, positioning it as a promising candidate for bone tissue engineering. Notably, hydroxyapatite (HA) formation was observed within 7 days of immersing the nanocomposite film in simulated body fluid (SBF), effectively mimicking natural bone mineralization. The PVA + SA@10 wt%TiO2NPs nanocomposite demonstrated potent antibacterial activity against S. aureus and E. coli, along with excellent cytocompatibility with MG-63 cells. Advanced characterization techniques, including FTIR, SEM, XRD, and analyses of swelling and porosity, confirmed significant improvements in physicochemical properties, supporting the superior performance of this composite. This scalable, cost-effective material holds substantial potential for advancing regenerative medicine by addressing critical orthopaedic challenges and offering a sustainable solution for bone tissue repair. The novelty of this work lies in the development of the PVA + SA@TiO2NPs composite film, specifically designed to enhance bone regeneration for orthopaedic applications.